Higher Education and the New Cold War - Marginson, Simon (International Higher Education, 2020)
For the past 40 years, there has been a high level of collaboration in science and technology between the United States and China. This cooperation has played a key role in China’s modernization and in research that furthers the global common good. This cooperation is now severely threatened by unilateral American moves.